The Clinical Assessment of Language Comprehension - Miller, Jon F.; Paul, Rhea (P.H. Brookes Pub. Co., 1995)
Keywords: Diagnosis; Language acquisition; Language disorders in children; Testing; dept.cmd; faculty_collection

Impairments of discourse abilities and executive functions in traumatically brain-injured adults. - Coelho, Carl A; Liles, Betty Z; Duffy, Robert J (Brain Injury, 1995)
Preliminary findings from an ongoing investigation of the potential relationship between narrative discourse performance and executive functions in adults with traumatic brain injuries (TBI) are reported. Narrative stories were elicited from 32 adults with TBI. Stories were analysed at three levels: sentence production, intersentential cohesive adequacy, and story episode structure. These measures were then correlated with scores from the Wisconsin Card Sorting Test (WCST), the primary measure of executive function. A significant correlation was noted between a factor score from the WCST and the measure of story structure, but not sentence production or cohesive adequacy. These results suggest that executive functions may be a promising avenue to pursue in the search for underlying causal factors of narrative discourse dysfunction and, therefore to better delineate the nature of communicative deficits secondary to TBI.
93 citations (Crossref) [2023-10-31] Place: England Coelho, C A. Communication Disorders Department, Southern Connecticut State University, New Haven 06515, USA.
Keywords: *Aphasia; Broca/di [Diagnosis]; *Brain Damage; Chronic/di [Diagnosis]; *Brain Injuries/di [Diagnosis]; *Neuropsychological Tests; *Problem Solving; *Speech Production Measurement; Adolescent; Adult; Aphasia; Broca/px [Psychology]; Aphasia; Broca/rh [Rehabilitation]; Brain Damage; Chronic/px [Psychology]; Brain Damage; Chronic/rh [Rehabilitation]; Brain Injuries/px [Psychology]; Brain Injuries/rh [Rehabilitation]; Female; Humans; Male; Middle Aged; adolescent; adult; article; brain injury; clinical article; dept.cmd; female; human; male; speech analysis; speech articulation; speech disorder

Discourse production deficits following traumatic brain injury: A critical review of the recent literature - Coelho, Carl A (Aphasiology, 1995)
This review analyses several recent studies of discourse deficits subsequent to traumatic brain injury. The review describes methodological problems related to incomplete subject descriptions, use of different discourse elicitation tasks and analyses, and examines the findings from each study by level of analysis. The limitations of these findings are discussed and general conclusions regarding discourse abilities following traumatic brain injury are offered. Implications for future research are also presented.
53 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/023-484-036-629-272 tex.type: [object Object]
Keywords: aphasia; brain injury; conversation; dept.cmd; dysarthria; human; injury scale; language disability; peer-reviewed; review